KEADILAN DALAM RETRIBUSI PARKIR BERLANGGANAN - Ahmad Munir; Moh. Hudi (Universitas Islam Darul Ulum, 2018)
The regional government has the authority to regulate and manage government affairs on the basis of regional autonomy. The presence of parking fees is one of the results of the regional autonomy regulation. Subscription parking levies are applied by various regions, but there is a contradiction with Law Number 28 of 2009 concerning Regional Taxes and Regional Levies and can harm the public. For this reason, it is necessary to study justice in the application of subscription parking fees. The methodology used is the legislative approach and the conceptual approach by examining legislation and doctrines relating to subscription parking fees. The purpose of this study is to examine and find appropriate regulations in the application of parking fees. The application of parking fees for subscription parking fees cannot be forced or required for all people because it is not in accordance with the concept of retribution and and the basis of justice. For this reason, the application of subscription parking cannot be forced on all parking retribution subjects to bring about of justice.